Kashf al-GharÄâ€™ib: Terjemahan atas Kitab Munfarijah Karya ImÄm Muá¸¥aqqiq AbÄ« Yaá¸¥yÄ Zayn al-DÄ«n ZakarÄ«yÄ - Syaukani, Syaukani (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2017)
An effort to preserve and utilize manuscripts in this archipelago, especially religious manuscripts, is very important due to, at least, two reasons. Firstly, there has been abundant important information pertinent to religious phenomena in the manuscripts. Secondly, physical condition of the manuscripts has been increasingly fragile. Following the process of choosing the manuscript, the author has selected one of the manuscripts preserved in the State Museum of North Sumatra. This study employs the theory of philology, literature and history in analyzing the manuscript. Analyses are focused on the language used, the cultural background of the manuscript, and the social history of the region where it has been written. The findings of this study tell us that the manuscript, named Kashf al-Ghar??ib, is a classical Islamic manuscript which still has been well preserved at the State Museum of North Sumatra. It contains the scientific information of fiqh (Islamic law), especially discussing about the way of worshipping the God. The manuscript also consists of religious poems and problems of adab (ethics). Of the three topics discussed in this manuscript, I give considerable attention on worship and ethical issues.